An evaluation of risk factors, clinical features, and follow-up findings of patients with infective endocarditis (Annals of Medical Research, 2021)
Aim: Infective endocarditis (IE) is a serious infection of the endocardial layer of the heart and the endothelial layer of the aorta,which usually is caused by bacteria or fungal microorganisms, requiring early diagnosis and treatment. Congenital heart diseases(CHD) and acquired valvular diseases are risk factors for IE. Advances in life-saving medical interventions such as intensive care,immunosuppressive treatments and the more frequent use of implanted prosthetic materials have increased the risk of IE.The aim of this retrospective study is to evaluate the underlying risk factors, clinical and laboratory findings, microbiological profiles,treatments, and follow-up of patients diagnosed with IE in our clinic.Material and Methods: In this retrospective study, risk factors, clinical features, laboratory findings, microbiological characteristics,echocardiographic features and medical treatment results and complications of 7 patients who admitted to Inonu University Facultyof Medicine Pediatric Cardiology Department a diagnosed with IE, between 2013-2019 were evaluated.Results: Seven patients who were diagnosed with IE were detected from the hospital data system. When the predisposing causeswere examined, we found that 3 patients had mitral insufficiency due to rheumatic heart disease, and 3 patients had CHD. Noneof our patients had a history of intervention before infective endocarditis. Bacteria grew in blood cultures of all patients. The mostgrown microorganisms were Staphylococci. Surgical treatment, valve repair or replacement therapy, was applied to three patients.A patient, who had aortic coarctation and mycotic aneurysm developing based on infective endarteritis, died on the 5th day due toaneurysm rupture while waiting for surgery under antibiotic pressure.Conclusion: Despite advancing treatment modalities, the mortality rate is about 25%, which is still too high. The most commonbacterial infections that cause IE are Streptococci and Staphylococcal infections. Since mortality and morbidity rates are too high inIE, in case of suspicion, necessary laboratory tests and blood cultures should be taken, and treatment should be started immediately.
Keywords: Child; congenital; endocarditis; heart defects